Answering the endocrine test questions. - Schmidt, C W (1999)
Evidence suggesting that certain chemicals may bind to endogenous hormone receptors and disturb normal endocrine functioning, thereby increasing the risk of reproductive problems and cancer in humans, has led to international efforts to screen chemicals for endocrine activity and potential health effects. The U.S. Environmental Protection Agency (EPA) has recommended that some 87,000 commercial chemicals for which there currently are inadequate toxicity data be evaluated. In December 1998, the EPA's Endocrine Disruptor Screening and Testing Advisory Committee (EDSTAC) recommended the use of a tiered system of screening and testing assays to sequentially eliminate chemicals for which further testing is deemed unnecessary. The first step toward implementing such a system-validation of the tests to be used-is presenting some challenges, however, with stakeholders disagreeing over which tests to validate, how extensively to validate them, and how much it will cost.